N. F. S. Grundtvig og »Rationalisterne« i årene 1825-32 - Rasmussen, Jens (Grundtvig-Studier, 1998)
Grundtvig and the »Rationalists« in the Years 1825-32 - Views and Development By Jens Rasmussen The article describes the development of Grundtvig’s view of the Church and of Baptism in the debate with the »Rationalists« in the period 1825-32, and not least Grundtvig’s positive promise to his readers, made in »Kirkens Gienmæle« (The Rejoinder of the Church), of a historical proof of the origin of the Apostles’ Creed in the Christian Church. In the entire conflict with his opponents - not least the Clausen family - Grundtvig described the leading theologians and clergymen as »Rationalists«, a much too unsubtle term which eventually came to preclude others from understanding what was his real purpose. Both moderate forces and prominent university scholars such as Professor H.N. Clausen had emphasized the overall importance of the Scriptures, in relation to the tradition and historical evidence of the Church. But not so Grundtvig. A distinct development in Grundtvig’s church view had taken place since 1825, with the discovery of the Church, partly as existing before Scripture, which assigns a special significance to Baptism and Communion, and partly as a community bound to the Apostolic Creed. In Grundtvig’s treatises in »Theologisk Maanedsskrift« (Theological Monthly) after »Kirkens Gienmæle« in 1825, his whole church view found its conclusion as early as 1828 in an understanding of the unchangeability of the baptismal covenant - everything was given already in Baptism through baptismal faith and baptismal covenant. Kaj Thaning dates this development conclusively to 1832, but it happens gradually already in the first years after the publication of »Kirkens Gienmæle«. In the years following 1825, Grundtvig showed uncertainty with regard to a historical proof, since the historical church evidence behind the Scriptures eluded ordinary historical demonstration. It was not a matter of a historical proof. A precondition, however, was the historical perspective: the living oral confession carried unbroken through time. It did not primarily have to do with history, but with the Church. The main emphasis was on »our Confession of Faith in Baptism«. What was essential was the defenceless Word from the Lord’s own mouth, as it was heard by everyone in the renunciation and faith of the baptismal covenant. Grundtvig came to recognize that the layman’s confession of faith in Baptism was »det ægte christelige« (genuine Christianity)- In the ritual debate of the 1830s - not least in the controversy over the baptismal ritual - Grundtvig maintained these views, and the line of development goes back to 1825.